2016
DOI: 10.1159/000447801
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origins of Disease - Crisis Precipitates Change

Abstract: The concept of developmental origins of diseases has gained a huge interest in recent years and is a constantly emerging scientific field. First observations hereof originated from epidemiological studies, linking impaired birth outcomes to adult chronic, noncommunicable disease. By now there is a considerable amount of both epidemiological and experimental evidence highlighting the impact of early life events on later life disease susceptibility. Albeit far from being completely understood, more recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 211 publications
(251 reference statements)
0
77
0
4
Order By: Relevance
“…So far, many different maternal programming factors have been discovered (for example over- or undernutrition [33-35], lack of micronutrients [36, 37], and stress during pregnancy [38-40]). However, more recent studies showed that also paternal exposure to adverse environmental conditions can act on the offspring’s phenotype in terms of fetal programming and influence later life disease risk [11, 28]. Paternal programming has been likewise described in clinical observation studies [41, 42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many different maternal programming factors have been discovered (for example over- or undernutrition [33-35], lack of micronutrients [36, 37], and stress during pregnancy [38-40]). However, more recent studies showed that also paternal exposure to adverse environmental conditions can act on the offspring’s phenotype in terms of fetal programming and influence later life disease risk [11, 28]. Paternal programming has been likewise described in clinical observation studies [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that gut microbiota is important in regulating metabolic pathways in healthy people and in patients with obesity, diabetes and cardiovascular diseases [8, 9]. The developmental origins of health and disease (DOHaD) hypothesis, firstly formulated in the early 1990s, proposed that adverse in utero conditions can influence developmental pathways in early life that result in long-term changes to offspring disease susceptibility [1, 2, 10, 11]. Recent work on the human microbiome indicates that gut microbiota may additionally explain the observations put forth by the DOHaD hypothesis [12-14].…”
Section: Introductionmentioning
confidence: 99%
“…Women with GDM have a higher risk of preeclampsia and cesarean section, [4,5] whereas complications for their newborns include a higher risk for macrosomia [5][6][7] and fetal hypoglycemia [4,8]. Potential long-term consequences for the health of mother [9][10][11] and child [10,12,13] may be an impaired glucose tolerance, obesity, and metabolic disorders. Even though GDM usually resolves after birth and blood glucose returns to normal levels, mothers that developed GDM during pregnancy have an increased risk for type 2 diabetes mellitus (T2DM) [14].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative hypothesis that might explain our findings would be that yet unknown environmental stimuli during human pregnancy might triggers epigenetic alterations of the human placenta or the vascular system including kidneys of the pregnant women [44][45][46][47][48][49] leading to an activation of the ET system in hypertensive pregnant women. An involvement of epigenetic mechanisms in the activation of the ET system has been described for diseases such as leukemia [50][51][52][53], cardiomyocyte terminal differentiation in the developing heart [54].…”
Section: Discussionmentioning
confidence: 92%